Firefly algorithm inspired energy aware clustering protocol for wireless sensor network. (2nd July 2019) - Bongale, Anupkumar M.; Nirmala, C.R.
Most of the existing cluster-based routing protocols focus either on cluster head election schemes or on refinement of routing process ignoring process of cluster formation. In this paper, firefly algorithm inspired energy aware clustering protocol for WSN is presented. The idea of the proposed protocol is to elect the cluster head nodes by assigning them intensity value defined through firefly algorithm. Another contribution of this paper is energy efficient cluster formation where cluster members join to cluster heads based on intensity parameter associated with cluster head. The presented protocol ensures that the elected cluster heads are usually located in densely populated area of the network resulting in low distance intra-cluster data transmissions and ultimately leading to low energy consumption. The firefly-based protocol is compared with popular routing protocols such as LEACH, LEACH-C and EOICHD and comparative results indicate that proposed protocol is highly energy efficient than other protocols.